2020
DOI: 10.1161/hypertensionaha.120.14959
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Expressing Cells Require β1-Integrin for Survival and for Development and Maintenance of the Renal Vasculature

Abstract: Juxtaglomerular cells are crucial for blood pressure and fluid-electrolyte homeostasis. The factors that maintain the life of renin cells are unknown. In vivo, renin cells receive constant cell-to-cell, mechanical, and neurohumoral stimulation that maintain their identity and function. Whether the presence of this niche is crucial for the vitality of the juxtaglomerular cells is unknown. Integrins are the largest family of cell adhesion molecules that mediate cell-to-cell and cell-to-matrix interactions. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Ablation of the renin cells via long-term conditional deletion of β 1 integrin prevents the arteriolar disease, indicating that renin cells are fully responsible for the arteriolar hypertrophy. In those mice at 4 months of age, the number of renin lineage cells was markedly decreased, consistent with the known role of Itgb1 in the prevention of anoikis and apoptosis in renin lineage cells ( 30 ). Similar results are obtained when renin cells are ablated in mice using diphtheria toxin genetically engineered to be expressed under the control of the renin gene ( 31 ).…”
Section: Discussionsupporting
confidence: 82%
“…Ablation of the renin cells via long-term conditional deletion of β 1 integrin prevents the arteriolar disease, indicating that renin cells are fully responsible for the arteriolar hypertrophy. In those mice at 4 months of age, the number of renin lineage cells was markedly decreased, consistent with the known role of Itgb1 in the prevention of anoikis and apoptosis in renin lineage cells ( 30 ). Similar results are obtained when renin cells are ablated in mice using diphtheria toxin genetically engineered to be expressed under the control of the renin gene ( 31 ).…”
Section: Discussionsupporting
confidence: 82%
“…Conditional deletion of Connexin 40 in renin-expressing cells led to mislocalization of JG renin cells and excessive secretion of renin, resulting to malignant hypertension ( Wagner et al, 2007 ). β 1-integrin is required for the development and function of renin cells, and its absence caused a marked decrease in the number of renin cells and vascular alterations ( Mohamed et al, 2020 ).…”
Section: Intrarenal Angiotensin Generation: Location Enzymes Substrat...mentioning
confidence: 99%
“…This concurs with the study using MIP-Cre to generate Itgb1 -knockout mice, which showed reduced islet vascularization (Win et al, 2020). The involvement of Itgb1 signaling in organ vascularization appears to be a universal requirement: as shown in pituitary endocrine epithelial cells and kidney cells, Itgb1-inactivation leads to vasculature loss (Mohamed et al, 2020; Scully et al, 2016). The expression of Vegfa , an essential growth factor for islet vasculature, is not affected in Itgb1 ΔEndo/ΔEndo islets (Table S2).…”
Section: Discussionmentioning
confidence: 99%